Baseline ambulatory knee kinematics are associated with changes in cartilage thickness in osteoarthritic patients over 5 years. Issue 9 (14th June 2016) - Favre, Julien; Erhart-Hledik, Jennifer C.; Chehab, Eric F.; Andriacchi, Thomas P.
Abstract: Although kinematic alterations during walking have been reported with knee osteoarthritis (OA), there is a paucity of longitudinal data, therefore limiting our understanding of the role of kinematics in OA development. This study tested the hypothesis that less knee extension angle and less posterior displacement of the femur relative to the tibia during the heel-strike portion of the gait cycle are associated with greater loss of medial cartilage thickness during a follow-up period of five years. This study also tested for associations between flexion–extension angle and anterior–posterior displacement during other periods of the gait cycle and 5-year cartilage thinning. 16 subjects with moderate medial knee OA were tested with gait analysis and MRI at baseline and had a follow-up MRI after 5 years. Linear regressions were used to assess the relationship between changes in cartilage thickness and baseline kinematics using Pearson correlation coefficients. Multivariate regressions were also performed to adjust for gender, baseline age, BMI, walking speed, Kellgren/Lawrence grade, and baseline knee pain score. As hypothesized, baseline knee flexion angle and femoral displacement during heel-strike and other gait cycle periods were significantly associated with medial femoral and tibial cartilage thinning at the 5 year follow-up; these associations were strengthened after adjustment for covariates. This study provided new insight into the pathogenesis of knee OA where baseline knee kinematics were associated with longitudinal disease progression. These results could serve as a basis for developing newer gait modification interventions to reduce the risk for developing knee OA.